Profil Rumah Sehat di Perumahan Swadaya Kelurahan Sendangmulyo, Kecamatan Tembalang - Syaeful, Hana Humaira; Esariti, Landung (Jurusan Perencanaan Wilayah dan Kota, 2023)
Residents of Sendangmulyo Village tend to live in small to medium scale housing which triggers problems related to housing quality which are usually found in self-help houses, namely houses built on the basis of community efforts and tend to produce irregular and unhealthy housing. This article aims to identify the existing condition of self-help housing based on healthy housing requirements according to the guidebook by the Ministry of Public Works and Housing and the Decree of the Minister of Health No. 829 of 1999 concerning Housing Health Requirements. The results of the study prove that self-help housing in RW 008 Sendangmulyo Village is still dominated by houses that are not healthy with lack of air quality and lighting systems in the house. Therefore, the level of comfort and welfare of the occupants of the house at the research location must be considered again. This study recommends that the Semarang City Government can be more detailed and clear in creating self-help housing development regulations. Furthermore, if possible, the regulation should be socialized to people who want to build their houses independently so that the physical condition of the existing house buildings in each self-help housing can be more in line with healthy home guidelines and there is no inequality between one house and another.